2020
DOI: 10.1055/s-0040-1709157
|View full text |Cite
|
Sign up to set email alerts
|

Interventional Management of Head and Neck Tumors

Abstract: Advancements in medical imaging and device technology allow minimal invasive procedures for the diagnosis and treatment of various disorders. For the management of tumors in head and neck region, these image-guided interventions play essential role in the often used multidisciplinary approach. Tissue sampling under ultrasound or computed tomography guidance is generally the first step to reach a pathological diagnosis. For head and neck tumors with high vascularity, embolization using particulate matter, liqui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 79 publications
0
10
0
Order By: Relevance
“…Preoperative embolization of highly vascularized head and neck tumors was first described in 1974 when Hekster et al reported that meningioma embolization could reduce the amount of bleeding at the time of surgery, increase the likelihood of successful tumor resection, and shorten the operative time and postoperative recovery period. 2 The benefit in regards to reducing intraoperative bleeding was more pronounced, especially for larger, high-grade, and more vascularized tumors such as paraganglioma, angiofibroma, hemangiopericytoma, meningioma, hemangioblastoma, schwannoma, juvenile nasopharyngeal angiofibroma, and hypervascular metastases. 2,4,14 There are several goals of preoperative embolization: (1) to control hardly accessible feeder arteries; 15 (2) to reduce intraoperative bleeding; 15 (3) to shorten procedural time; (4) to increase the chances of successful total resection; 4 (5) to reduce the damage of surrounding normal tissue; 16 (6) palliative therapy to reduce intractable pain; 17 (7) to reduce tumor recurrence; (8) to improve visualization of the surgical field.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Preoperative embolization of highly vascularized head and neck tumors was first described in 1974 when Hekster et al reported that meningioma embolization could reduce the amount of bleeding at the time of surgery, increase the likelihood of successful tumor resection, and shorten the operative time and postoperative recovery period. 2 The benefit in regards to reducing intraoperative bleeding was more pronounced, especially for larger, high-grade, and more vascularized tumors such as paraganglioma, angiofibroma, hemangiopericytoma, meningioma, hemangioblastoma, schwannoma, juvenile nasopharyngeal angiofibroma, and hypervascular metastases. 2,4,14 There are several goals of preoperative embolization: (1) to control hardly accessible feeder arteries; 15 (2) to reduce intraoperative bleeding; 15 (3) to shorten procedural time; (4) to increase the chances of successful total resection; 4 (5) to reduce the damage of surrounding normal tissue; 16 (6) palliative therapy to reduce intractable pain; 17 (7) to reduce tumor recurrence; (8) to improve visualization of the surgical field.…”
Section: Discussionmentioning
confidence: 99%
“…2 The benefit in regards to reducing intraoperative bleeding was more pronounced, especially for larger, high-grade, and more vascularized tumors such as paraganglioma, angiofibroma, hemangiopericytoma, meningioma, hemangioblastoma, schwannoma, juvenile nasopharyngeal angiofibroma, and hypervascular metastases. 2,4,14 There are several goals of preoperative embolization: (1) to control hardly accessible feeder arteries; 15 (2) to reduce intraoperative bleeding; 15 (3) to shorten procedural time; (4) to increase the chances of successful total resection; 4 (5) to reduce the damage of surrounding normal tissue; 16 (6) palliative therapy to reduce intractable pain; 17 (7) to reduce tumor recurrence; (8) to improve visualization of the surgical field. 18 Considering that hemangioma is a type of tumor with high vascularity, preoperative tumor embolization was performed to reduce intraoperative risk and maximize the success of resection.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations